2005
DOI: 10.5424/sjar/2005031-130
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of rosmarinic and carnosic acids in rosemary extracts. Analysis of their in vitro antiradical activity

Abstract: Rosemary plants were analysed using HPLC and eight different compounds (vanillic acid, caffeic acid, rosmarinic acid, naringin, hispidulin, cirsimaritin, carnosol and carnosic acid) were identified and quantified. The analysis of the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity revealed that rosmarinic and carnosic acids were the best rosemary scavengers with IC sun(50) values of 27 and 32 micro M, respectively. Environmental influences on rosmarinic and carnosic acids content in rosemary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 18 publications
10
59
0
Order By: Relevance
“…Food material such as oil, raw and cooked meat, and cooked meat patties were protected from oxidation by carnosic acid, in most cases with a higher efficiency than synthetic antioxidants (Erkan et al, 2008;Zhang et al, 2010;Naveena et al, 2013;Jordán et al, 2014). Carnosic acid also was described as a scavenger of hydroxyl and 2,2-diphenyl-1-picrylhydrazyl radicals (Aruoma et al, 1992;Luis and Johnson, 2005). While the potential antioxidative activity of carnosic acid is well documented, its exact mechanism of action has not been studied extensively.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Food material such as oil, raw and cooked meat, and cooked meat patties were protected from oxidation by carnosic acid, in most cases with a higher efficiency than synthetic antioxidants (Erkan et al, 2008;Zhang et al, 2010;Naveena et al, 2013;Jordán et al, 2014). Carnosic acid also was described as a scavenger of hydroxyl and 2,2-diphenyl-1-picrylhydrazyl radicals (Aruoma et al, 1992;Luis and Johnson, 2005). While the potential antioxidative activity of carnosic acid is well documented, its exact mechanism of action has not been studied extensively.…”
mentioning
confidence: 99%
“…Carnosic acid is present at very high concentrations, up to several percent of dry weight, in leaves of the Mediterranean half-shrub rosemary (Munné-Bosch and Alegre, 2001;del Baño et al, 2003;Luis and Johnson, 2005). Carnosic acid biosynthesis and accumulation take place exclusively in young rosemary leaves at the branch apices, with the diterpene molecule being partially consumed during leaf development and aging (Hidalgo et al, 1998;Brückner et al, 2014;Bo zi c et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Literature studies on quantification of the amount of phenolic compounds in extracts of rosemary leaves have shown that the most abundant compounds were carnosic acid (CA) and rosmarinic acid (RA) followed by carnosol (CA-OH); the concentrations of the three compounds were found to be 12.18, 2.15 and 0.53 mg g -1 fresh weight biomass [24] and these were estimated to account for >90% of the antioxidant activity of the plant [25,26]. Commercial rosemary extract containing rosmarinic acid (93.4% pure) was used as the starting material for the synthesis of the rosmarinates esters investigated and reported here.…”
Section: Quantification Of Carnosic Acid Rosmarinic Acid and Carnosomentioning
confidence: 99%